1995
DOI: 10.1136/bmj.311.7004.558
|View full text |Cite
|
Sign up to set email alerts
|

How To Do It: Service provision and use of anticoagulants in atrial fibrillation

Abstract: Several large trials have shown that the risk of stroke in patients with non-valvar atrial fibrillation is reduced by treatment with warfarin. Implementing this research evidence requires not only an understanding of the trials' results and of the changes that they imply for clinicians' treatment decisions but also an appreciation of the organisation, quantity, and quality of services required to support these changes. Understanding of these implications is crucial for developing services that allow changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
(45 reference statements)
1
49
1
1
Order By: Relevance
“…Nevertheless this procedure may be valuable for detecting adjunctive pathology and, as the results show, in the low/intermediate risk groups about 32% had some marker of increased stroke risk with an ECHO. The overall rate of anticoagulation was higher than the 23% found by Sudlow et al, and the 31% by Karla et al 15,16 The Scottish Continuous Morbidity Recording Service database demonstrated that only 40% of patients were anticoagulated. In the study by Majeed and colleagues the rate of anticoagulation was around 30%.…”
Section: Discussioncontrasting
confidence: 40%
“…Nevertheless this procedure may be valuable for detecting adjunctive pathology and, as the results show, in the low/intermediate risk groups about 32% had some marker of increased stroke risk with an ECHO. The overall rate of anticoagulation was higher than the 23% found by Sudlow et al, and the 31% by Karla et al 15,16 The Scottish Continuous Morbidity Recording Service database demonstrated that only 40% of patients were anticoagulated. In the study by Majeed and colleagues the rate of anticoagulation was around 30%.…”
Section: Discussioncontrasting
confidence: 40%
“…There is an increased cost of managing patients in primary care and at no point did primary care become a lower cost option than secondary care. Local decision-makers need to assess the increased cost of primary care anticoagulation management in terms of the potential reductions in high-cost serious adverse events.Keywords: economic evaluation, anticoagulation, warfarin, primary care, secondary care.The continuing expansion of clinical indications for warfarin (particularly non-rheumatic atrial fibrillation) has greatly increased the pressure on hospital anticoagulation management services (Sudlow et al, 1995;Sweeney et al, 1995). In response, various efforts have been undertaken to provide care in non-hospital settings.…”
mentioning
confidence: 99%
“…The continuing expansion of clinical indications for warfarin (particularly non-rheumatic atrial fibrillation) has greatly increased the pressure on hospital anticoagulation management services (Sudlow et al, 1995;Sweeney et al, 1995). In response, various efforts have been undertaken to provide care in non-hospital settings.…”
mentioning
confidence: 99%
“…These issues are important in clinical practice for estimating the extent of need and the level or type of services required to initiate and monitor anticoagulation. 25 This study highlights the need for clear and simple guidelines for risk assessment that are age sensitive and allow unequivocal treatment decisions to be taken, using a standardized risk-assessment algorithm. There is little doubt that such consensus will improve the efficacy and effectiveness of anticoagulation and allow precise quantification of service resource needs.…”
Section: Discussionmentioning
confidence: 99%